2004
DOI: 10.1111/j.1744-7410.2004.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong character incongruence and character choice in phylogeny of sea stars of the Asterinidae

Abstract: Abstract. Historically, characters from early animal development have been a potentially rich source of phylogenetic information, but many traits associated with the gametes and larval stages of animals with complex life cycles are widely suspected to have evolved frequent convergent similarities. Such convergences will confound true phylogenetic relationships. We compared phylogenetic inferences based on early life history traits with those from mitochondrial DNA sequences for sea stars in the genera Asterina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Successive evolutionary transitions would then have occurred to give rise to various types of nonfeeding larval development by (a) loss of larval feeding structures such as ciliated bands and functional gut, and gain of large, yolky eggs, followed by (b) loss of planktonic dispersal, and then (c) gain of parental brood protection. Recently, however, molecular phylogenetic studies conducted on the family Asterinidae (Hart et al, 1997(Hart et al, , 2004 showed that ordered transformations between the four modes of development comprising brachiolariae (i.e., planktotrophic-pelagic, leci-thotrophic-pelagic, lecithotrophic-benthic, and lecithotrophic-intragonadal) could not be easily reconstructed, and that many parallel changes in larval form, habitat, and dispersal potential occurred. For example, in this family, benthic lecithotrophy evolved three times independently, in Parvulastra (Patiriella) exigua, in Aquilonastra (Asterina) minor and in the two sister species, Asterina gibbosa and Asterina phylactica (Hart et al, 2004;Byrne, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successive evolutionary transitions would then have occurred to give rise to various types of nonfeeding larval development by (a) loss of larval feeding structures such as ciliated bands and functional gut, and gain of large, yolky eggs, followed by (b) loss of planktonic dispersal, and then (c) gain of parental brood protection. Recently, however, molecular phylogenetic studies conducted on the family Asterinidae (Hart et al, 1997(Hart et al, , 2004 showed that ordered transformations between the four modes of development comprising brachiolariae (i.e., planktotrophic-pelagic, leci-thotrophic-pelagic, lecithotrophic-benthic, and lecithotrophic-intragonadal) could not be easily reconstructed, and that many parallel changes in larval form, habitat, and dispersal potential occurred. For example, in this family, benthic lecithotrophy evolved three times independently, in Parvulastra (Patiriella) exigua, in Aquilonastra (Asterina) minor and in the two sister species, Asterina gibbosa and Asterina phylactica (Hart et al, 2004;Byrne, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, molecular phylogenetic studies conducted on the family Asterinidae (Hart et al, 1997(Hart et al, , 2004 showed that ordered transformations between the four modes of development comprising brachiolariae (i.e., planktotrophic-pelagic, leci-thotrophic-pelagic, lecithotrophic-benthic, and lecithotrophic-intragonadal) could not be easily reconstructed, and that many parallel changes in larval form, habitat, and dispersal potential occurred. For example, in this family, benthic lecithotrophy evolved three times independently, in Parvulastra (Patiriella) exigua, in Aquilonastra (Asterina) minor and in the two sister species, Asterina gibbosa and Asterina phylactica (Hart et al, 2004;Byrne, 2006). In these species, brachiolariae all possess a hypertrophied attachment complex (Ludwig, 1882;MacBride, 1896;Komatsu et al, 1979;Marthy, 1980;Byrne, 1995Byrne, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Echinodermata, the Asterinidae, a major family of sea stars, is particularly noted for its diverse life histories (Byrne and Cerra, 1996;Hart et al, 1997Hart et al, , 2003Hart et al, , 2004Byrne et al, 1999a). Species in the asterinid genera Patiriella and Cryptasterina exhibit a range of developmental modes, including a most derived method of propagation-incubation of progeny in the gonads and birth of juveniles (Byrne, 1996;Byrne and Cerra, 1996;Byrne et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Predicting which morphological characters accurately reflect evolutionary relatedness (i.e., those exhibiting variation based on genetic factors) and which characters do not has proven difficult in sponge taxonomy. The use of molecular data in conjunction with traditional morphological analyses may provide a means of elucidating which morphological characters are homologous and diagnostic and which are homoplasic and uninformative (Alvarez et al 2000;Hart et al 2004).…”
mentioning
confidence: 99%